2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6385685
|View full text |Cite
|
Sign up to set email alerts
|

Multi-domain monitoring of marine environments using a heterogeneous robot team

Abstract: Abstract-In this paper we describe a heterogeneous multirobot system for assisting scientists in environmental monitoring tasks, such as the inspection of marine ecosystems. This team of robots is comprised of a fixed-wing aerial vehicle, an autonomous airboat, and an agile legged underwater robot. These robots interact with off-site scientists and operate in a hierarchical structure to autonomously collect visual footage of interesting underwater regions, from multiple scales and mediums. We discuss organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 13 publications
(17 reference statements)
0
54
0
Order By: Relevance
“…al. [39]. In their paper titled "Multi-domain monitoring of marine environments using a heterogeneous robot team," Shkurti et.…”
Section: Robot Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [39]. In their paper titled "Multi-domain monitoring of marine environments using a heterogeneous robot team," Shkurti et.…”
Section: Robot Collaborationmentioning
confidence: 99%
“…Deploying a robot team comprised of a ground and an aerial vehicle enables an enhanced field of view while maintaining safe navigation and localization. Recent advances in robotics have made collaboration among a heterogeneous team of robots possible [39]. At the same time, many interesting problems associated with multi-robot collaborative exploration are being discussed, such as coordination, communication protocols, bandwidth constraints, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These benefits have attracted many researchers from academia and industry to investigate the applicability of MRS in many pertinent areas of industrial and commercial importance such as intelligent security [1], search and rescue [2], surveillance [3], humanitarian demining [4], environment monitoring [5,6] and health care [7].…”
Section: Introductionmentioning
confidence: 99%
“…Research has already demonstrated the eectiveness of combining aerial and aquatic robotic operation by coordinating separate systems as a team for the monitoring of coral reefs [13], with an MAV using aerial video footage to guide and augment close observation by an aquatic vehicle. Murphy et al [10] also found that use of the MAV provided a more eective communication relay with the surface vehicle.…”
Section: Introductionmentioning
confidence: 99%